2015
DOI: 10.7771/2157-9288.1102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Engineering Camp on Students’ Perceptions of Engineering and Technology

Abstract: Students' knowledge about a profession influences their future decisions about careers. Research indicates that students tend to hold stereotypical views of engineers, which would hinder engineering as a career choice. The purpose of this study was to measure how participating in a week long engineering summer camp affected middle school students' (N519) attitudes towards engineering and their conceptions of engineering and technology. Results indicate that participation in the programs had a positive impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 30 publications
2
44
0
3
Order By: Relevance
“…In a later study, they found that elementary students' categorizations were improved after completing an Engineering is Elementary unit (Museum of Science, Boston) (Cunningham & Lachapelle, 2007). A similar version of the activity-categorization task was also used by Hammack, Ivey, Utley, and High (2015), who found evidence of misconceived views among middle-school students. Ozogul, Miller, and Reisslein (2017) used a different categorization task with K-5 students and found that older students tended to have fewer misconceptions than younger students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a later study, they found that elementary students' categorizations were improved after completing an Engineering is Elementary unit (Museum of Science, Boston) (Cunningham & Lachapelle, 2007). A similar version of the activity-categorization task was also used by Hammack, Ivey, Utley, and High (2015), who found evidence of misconceived views among middle-school students. Ozogul, Miller, and Reisslein (2017) used a different categorization task with K-5 students and found that older students tended to have fewer misconceptions than younger students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other instruments have been developed to approach the problem from different angles. Researchers have asked elementary and middle school students to explain their perceptions of engineering and technology in an instrument containing pictures and images as well as open-ended questions about engineering and technology as defined by the participant [33,34]. While a comparison of perceptions from teacher and student perspectives is outside the scope of this study, it further illustrates the gap in the literature about secondary science preservice teachers' perspectives.…”
Section: Instruments To Measure Perceptionsmentioning
confidence: 99%
“…Deney grubu öğrencilerinden ön testte mühendislikle ilgisi olmayan yanlış bir çizim yapanların sayısının son testte azaldığı görülmüştür. Alan yazında mühendislik uygulamalarının (Hammack, Ivey, Utley ve High, 2015;Lyons ve Thompson, 2005;Sabo, Burrows ve Childers, 2014) ve entegre programların (Yoon vd., 2014) mühendislikle ilgili algıyı doğru yönde geliştirdiğini belirterek bu sonucu destekleyen araştırmalar bulunmaktadır. Deney grubu öğrencileri ön testte çoğunlukla "ev/inşaat yapan","bilgisayarla uğraşan" mühendis çizerken; son testte "çizim/tasarım yapan", "şehir planlaması yapan" algısına geçiş yaptıkları görülmüştür.…”
Section: Tartışma Sonuç Ve öNerilerunclassified